Fear of aging among young people - Danijela Lahe; Maja Hmelak (Nova Prisutnost)
Fear is a natural emotion that individuals experience throughout their lives. Growing up, fear manifests itself in the emotions, behaviour and actions of young people, often associated with stressors such as fear of failure, social problems or too high expectations. Among the most important fears at a young age is the fear of death (thanatophobia), which can intensify anxiety and stress, especially when combined with social media pressures. In addition, the fear of aging (gerontophobia) stems from existential concerns about mortality and the social stigmatization of aging. Addressing these fears through psychological interventions, confidence building, and cultural coping mechanisms is key to reducing anxiety and building resilience. For the purposes of the research, a quantitative methodology with an online survey was used. Primary and secondary sources were collected, analysed and synthesized. Primary data were obtained through a survey aimed at Slovenian secondary school students. Secondary sources were obtained from professional literature and websites. The survey sample included 1,234 respondents aged between 15 and 29, including high school and university students. The data collection was carried out using the method of improbable (occasional) sampling. To ensure representativeness, data were weighted by gender. Statistical analysis, including descriptive and multivariate analysis, was performed with the SPSS 21 program, where the internal consistency of the scales was measured with the Cronbach alpha coefficient. With the research, the authors wanted to check whether there is a fear of aging among young people. It turned out that the average fear of loss is 51.2%, while the fear of physical appearance and psychological worries is present in 20.5% and the fear of the elderly in 6.7%. Statistically significant differences were found in terms of gender, status, place of residence and frequency and quality of contacts with the elderly, indicating the complexity of factors that influence the fear of aging.